Kepastian Hukum Perkawinan Beda Agama di Indonesia - Sumarna, Reza; Rifai, Anis; Fuad, Fokky (Jurnal Bedah Hukum, 2025)
Marriage is one way to obtain a partner and offspring so that Indonesia has regulations that emphasize marriage with the same beliefs, Indonesian society is diverse including in terms of religion, many establish relationships and marry with couples of different religions. The problem such as the desire to even have an interfaith marriage, this is crucial for the legal position of interfaith marriage in Indonesia and how the legal certainty of interfaith marriage in Indonesia after the issuance of SEMA No. 2 of 2023 considering that there are already several District Courts that allow interfaith marriage. This study aims to provide clarity on the legal position, interfaith marriage status, the attitude of judges in giving court decisions and deciding interfaith marriages after the issuance of SEMA No. 2 of 2023 in order to achieve legal certainty in the onslaught of interfaith marriages which are the implications and pluralism of Indonesian society. The method used is normative research by taking into account the discipline of Law, in addition to researching literature using legal materials as sources which include primary legal materials, secondary legal materials and tertiary legal materials. The results of the study clarify the legal certainty of interfaith marriage after the issuance of SEMA No. 2 of 2023, especially against the Marriage Law which clearly prohibits interfaith marriage, it can be said that interfaith marriages that have been recorded are invalid and have no legal force or will be null and void because they conflict with existing regulations.